Family firm heterogeneity on CSR approach: A socio-emotional (SEW) perspective - Julio Diéguez-Soto; Marta Campos-Valenzuela; Ángela M. Callejón-Gil; Ignacio Aldeanueva-Fernández (BRQ Business Research Quarterly, 2024)
How family firms adopt a certain corporate social responsibility (CSR) approach remains a relatively unexplored matter in family firm and firm ethics research. Hence, we study how and why the CSR approach (broad vs. narrow; benefits vs. costs) differs within family firms, addressing the influence of the socio-emotional wealth (SEW) dimensions, individually or combined. We used empirical evidence gathered through 13 case studies of firms from the Andalusia region and we used the interpretative approach of the grounded theory based on case study data. Results of our analyses lead to propose that family firms with a higher identification and more positive than negative valence with regard to emotional attachment and family enrichment dimensions will be more likely to exhibit a broad approach of CSR. Likewise, those family firms adopting CSR actions with stakeholders due to instrumental use of image and reputation dimension will more probably display a benefits approach.
Keywords: L26; M14; 650; Socio-emotional wealth; family firm; CSR approach; case study